2005
DOI: 10.17221/5622-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mycoplasma contamination in cell cultures and bovine sera

Abstract: Contamination of cell cultures and sera used for animal virus propagation with mycoplasmas represents a serious problem, especially in virology. Therefore specific control measures must be used. To achieve this we introduced PCR for the detection of mycoplasma species in cell cultures and compared its results with ELISA and microbiological culture. Seven mycoplasma species which are the most common contaminants of cell lines (Mycoplasma arginini, M. fermentans, M. hyorhinis, M. bovis, M. orale, M. hominis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Although there is not much information about the expected rate of contamination, some authors have reported 0-19% of FBS batches to be positive for mycoplasma. 1,2,6,9,22 Our pestiviral RT-rtPCR results indicated that a high proportion (84%) of the FBS batches contained viral RNA. Our data are in accordance with previous studies; multiple authors have reported pestiviral contamination rates of 22-100% in commercial FBS batches.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although there is not much information about the expected rate of contamination, some authors have reported 0-19% of FBS batches to be positive for mycoplasma. 1,2,6,9,22 Our pestiviral RT-rtPCR results indicated that a high proportion (84%) of the FBS batches contained viral RNA. Our data are in accordance with previous studies; multiple authors have reported pestiviral contamination rates of 22-100% in commercial FBS batches.…”
Section: Discussionmentioning
confidence: 80%
“…The most likely sources of cell culture contamination with mycoplasma appear to be laboratory personnel, FBS, and other infected cell cultures. 9,17 Microbiologic culture is the gold standard test to detect every kind of mycoplasma contamination in cell cultures without considering the origin and species of mycoplasma. However, culture is time-consuming and may lead to false-negative results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials such as cell seed, virus seed, tissue culture medium, fetal bovine serum [13] were screened qualitatively for the mycoplasma contamination by polymerase chain reaction before initiating any activity. The detection of mycoplasma through PCR is sensitive, rapid and suitable method for the cell culture facility [14]. This primer pairs can able to detect the species of mycoplasma, (Mycoplasma fermentans, Mycoplasma hyorhinis, Mycoplasma arginini, Mycoplasma orale, Mycoplasma salivarium, Mycoplasma hominis, Mycoplasma pulmonis, Mycoplasma arthritidis, Mycoplasma neurolyticum, Mycoplasma hyopneumoniae,Mycoplasma capricolum) and one species Ureaplasma (Ureaplasma urealyticum) with specific amplified product for each species.…”
Section: Mycoplasma Detectionmentioning
confidence: 99%
“…The contamination can cause disastrous effects on eukaryotic cells as it tends to alter the cells at a molecular level and compromises the value of the contaminated cell lines in providing accurate data for life science research. It can induce alterations in cellular parameters (e.g., chromosome aberrations, changes in metabolism and cell growth) leading to unreliable experimental results and potentially unsafe biological products [ 2 , 3 ]. In cell culture laboratories, infection usually occurs with the same mycoplasma species, and this proves that mycoplasma infections are often spread from one culture to another [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%